Climate-Resilient Infrastructure Planning Strategies: A Literature Review from a Civil Engineering Perspective - Fitri; Edhi Kurniawan; Andi Hasri Tri Ulandari; Muh Tegar Febrian (Jurnal Teknik Sipil, 2026)
Climate change has intensified the risk of infrastructure system failures due to extreme rainfall events, sea-level rise, and the increasing frequency of hydrometeorological hazards. Conventional design approaches based on historical data are no longer sufficient to address such uncertainties; therefore, more adaptive and long-term resilience-oriented planning strategies are required. Although numerous studies have examined climate-resilient infrastructure, comprehensive reviews that synthesize these strategies from an integrated civil engineering perspective remain limited. This study aims to identify the evolution of climate-resilient infrastructure planning strategies and to classify these approaches into technical, managerial, and policy dimensions. A qualitative approach was employed using a narrative literature review method, analyzing 72 national and international publications published between 2014 and 2025. The analysis was conducted through thematic categorization to map emerging patterns of planning strategies within the civil engineering literature. The findings indicate that adaptive infrastructure planning involves adjustments to design parameters and the implementation of performance-based design, the integration of risk management throughout the infrastructure life cycle, and the strengthening of regulatory frameworks and climate adaptation policies. The integration of these three dimensions is essential to developing robust and sustainable infrastructure systems. This study proposes an integrated conceptual framework that can support the advancement of climate-resilient infrastructure development in Indonesia.